2018
DOI: 10.1111/pin.12659
|View full text |Cite
|
Sign up to set email alerts
|

A lesion categorized between ghost cell odontogenic carcinoma and dentinogenic ghost cell tumor with CTNNB1 mutation

Abstract: Ghost cell odontogenic carcinoma (GCOC) is a rare malignant neoplasm characterized by the presence of ghost cells. It is considered to arise either de novo or from a preexisting benign precursor, calcifying odontogenic cyst (COC), or dentinogenic ghost cell tumor (DGCT). We report a case of a 44-year-old Japanese male with a left maxillary tumor. The patient received treatment to resect the left maxillary cyst 25 years prior; however, the details were uncertain. The tumor was resected with clear margins. Taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…We recently reported that 10 out of 11 patients with calcifying cystic odontogenic tumors (calcifying odontogenic cyst) have mutations in the CTNNB1 gene, while 12 out of 14 patients with ameloblastoma have mutations in the BRAF gene [10]. We also reported a patient with ghost cell odontogenic carcinoma with a mutation in the CTNNB1 gene, suggesting that CTNNB1 gene mutations are one of the common features of lesions accompanied by ghost cell keratinization [11]. These findings confirmed that genetic alterations not only provide valuable information on oncogenesis but also contribute to the diagnosis and classification of odontogenic lesions.…”
Section: Discussionmentioning
confidence: 94%
“…We recently reported that 10 out of 11 patients with calcifying cystic odontogenic tumors (calcifying odontogenic cyst) have mutations in the CTNNB1 gene, while 12 out of 14 patients with ameloblastoma have mutations in the BRAF gene [10]. We also reported a patient with ghost cell odontogenic carcinoma with a mutation in the CTNNB1 gene, suggesting that CTNNB1 gene mutations are one of the common features of lesions accompanied by ghost cell keratinization [11]. These findings confirmed that genetic alterations not only provide valuable information on oncogenesis but also contribute to the diagnosis and classification of odontogenic lesions.…”
Section: Discussionmentioning
confidence: 94%
“…[ 25 ] Recent studies reported higher number of malignant epithelial cells expressing cytokeratin, Ki-67 and p53. [ 24 29 34 38 43 45 48 ] In cases reported by Zhu et al . the positive expression rate of Ki-67 was 61.8% which indicates that cell proliferation activity is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…1) [3]. The MAPK pathway is implicated in ameloblastoma and adenomatoid odontogenic tumor, the SHH pathway implicated in ameloblastoma and odontogenic keratocyst, formerly termed keratocystic odontogenic tumor (OKC/KCOT), and the Wnt signaling pathway in the family of odontogenic ghost cell tumors [4][5][6][7][8][9].…”
Section: Recent Developments In Our Understanding Of Odontogenic Tumomentioning
confidence: 99%
“…DGCT is characterized by a benign solid epithelial component, ghost cells, and sheets of dentinoid [22]. Abundant mitoses, perineural, or angiolymphatic invasion are features that may be present in GCOC; however, the distinction between DGCT and GCOC may be challenging when overt features of malignancy are lacking [9]. GCOC may arise de novo or from malignant transformation of DGCT or COC/ CCOT.…”
Section: Recent Developments In Our Understanding Of Odontogenic Tumomentioning
confidence: 99%